Applications of vertical cavity surface emitting lasers for low-pressure chemical vapor deposition reactors. (October 2019) - Noh, Youngsu; Kim, Yoonsuk; Park, Seungho; Kim, Byung-Kuk; June Kim, Hyoung
Highlights: Design of a LPCVD reactor using high-power VCSEL modules. Optimal placement of VCSEL modules ensuring uniform irradiation on wafers. Factors for the Arrhenius equation depicting the deposition process. Simulation of the LPCVD process of poly-Si thin-film on 300 mm Si wafers. Minimization of the wafer exclusion region by controlling local VCSEL emission. Abstract: Vertical cavity surface emitting lasers (VCSELs) with a wavelength of 980 nm were applied to design a low-pressure chemical vapor deposition (LPCVD) reactor as a promising heat source of excellent irradiation uniformity, rapid power controllability, and extended spatial scalability. The average divergence angle of the laser beam emitted from a myriad of cells was estimated from a comparison of the VCSEL emission distribution obtained from ray-tracing calculation with experimental measurements using a power meter. This property was closely related to irradiation uniformity and spatial scalability. The experimental temperature distribution of silicon wafers exposed to high power VCSEL beams was used to verify the performance of commercial codes on three-dimensional simulation models including conduction, convection and thermal radiation. For LPCVD reactor design, this code was used to predict the optimal placement of the VCSEL module for uniform irradiation on 300 mm diameter wafers. The best-fit values of the factors for the Arrhenius equation describing the deposition process of polycrystalline silicon (poly-Si) thin-film using silane gas species were obtained from a comparison of deposition rates from numerical simulations with experimental observations available in the literature. Using these factors and the optical characteristics of the VCSEL and Si, the deposition process on the wafer with 300 mm in diameter was simulated under various operation conditions. Especially, instead of the uniform surface temperature condition, the heat flux distribution estimated from experimental irradiations on the wafer was used for the boundary condition at the bottom surface of the wafer in order to realize a practical deposition process. Simulation using the realistic heat flux boundary conditions showed that deposition rates in the wafer edge-region were significantly reduced due to the severe temperature drop in that region, compared to that using the ideal uniform temperature condition. In order to minimize this wafer exclusion area, the emission power of the VCSEL emitters affecting the wafer edge-region was adjusted to slightly increase, resulting in a more uniform distribution of the deposition rate.